PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA DOSEN (Pada Universitas Islam Maulana Malik Ibrahim Malang) - Silvia Zahrotul Badiah; Hadi Sunaryo; pardiman pardiman (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT The purpose of this study was to determine the effect of intellectual intelligence, emosional intelligence, and spiritual intellegenceon the performance of lecturers at the state University of Maulana Malik Ibrahim in this study the sample was taken as many as 102 respondents who where PNS permanent lecturers. The method of analiysis used in this study is teh method of multiple linier regression analysis with hypoyhesis testing using teh F test and t test. The results of this study incicate the intellectual intellegence, emotional intellegence, and spiritual intellegence have a significant or joint effect (simultan) on the performance of lecturers. Key word : intellectual intellegence, emotional intellegence, and spiritual intellegence.